Dampak Perubahan Nilai Mata Uang Rupiah Terhadap Indeks Pasar Modal Indonesia Dimoderasi Fluktuasi Covid-19 - Elvi Rahmayanti; Maha Martabar Mangatas Lumbanraja (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
The growth of the Capital Market has become an alternative for investors, especially novice investors, which is developing along with increasing financial literacy, and the presence of behavioral change factors driven by the Covid-19 Pandemic. This growth was also evident from the increasing volume of trade during the pandemic, both in the Capital Market and the Rupiah Exchange Rate Market, which was allegedly caused by the Covid-19 Pandemic conditions in Indonesia. The population in this study is data on stock exchange 145 working days which range from 1 January 2022 to 12 August 2022, which is analyzed using the Partial Least Square (PLS) approach. The results showed that Covid-19 strengthened the effect of currency exchange rates on the JCI, while Covid-19 weakened the effect of the rupiah exchange rate on LQ-45 and Kompas-100.